Bimbingan Teknis Pembuatan Pupuk Kompos ditengah Covid 19 pada Kawasan Persawahan Amohalo Kelurahan Baruga Kecamatan Baruga Kota Kendari: Technical Guidance for the Making of Compost Fertilizer in the Middle of Covid 19 in Amohalo Rice Area, Baruga Subdistrict, Baruga Subdistrict, Kendari City - Abadi, Musram; Faslih, Arman; Sisworo, Raden Rinova; Umar, Muhammad Zakaria; Aminur, Aminur; Saparun, Moh. (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The Amohalo rice field area is one of the rice fields in the Baruga Village, Baruga District, Kendari City, Southeast Sulawesi Province. The people of the Amohalo rice field area RT 09 RW 08, Baruga Village, generally make a living as rice farmers. In addition to making a living as a farmer, the Amohalo community in Baruga Village also has livestock such as chickens and cows. The local community does not utilize waste in the form of costs from a relatively abundant amount. Applying appropriate technology in an integrated manner to compost can provide benefits as organic fertilizer for plants. Community Service Program Integrated Lecturers Thematic KKN is conducted for one month, August-September 2021. This program is carried out in several stages of implementation, namely: (1) the Preparation stage for recruitment, coordination with related parties and correspondence, assistance needs, and preparation of instruments, (2) The stage of socialization of the determination and place of socialization, as well as a debriefing of students participating in the Thematic KKN, (3) The implementation phase includes counseling and training, technical guidance, and reporting. The results achieved in this Thematic Community Service Program are an increase in public knowledge and understanding of agricultural and livestock waste by processing it into compost to increase farmer productivity and reduce the impact of livestock by-products.